Changes in Productivity of the Colombian Banking Sector during 2002-2016 (2021)
In this paper the evolution of the productivity of banks in Colombia from 2002 to 2016 is studied through the application of the non-parametric methodology of the Malmquist index of Data Envelopment Analysis (DEA), generating relative efficiency indicators for the banks for each period, throughout the fifteen years of the study. The results show that in 64% of the periods the average productivity improved, and the period 2003-2004 had the best result, since during this time the Colombian banking sector was in full development and consolidation. Additionally, in four periods there was a decrease in average productivity, the greatest decrease occurred between 2009 and 2010, during the first world financial crisis of this century.